2017
DOI: 10.1097/md.0000000000007484
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of urinary [TIMP-2]·[IGFBP7] for acute kidney injury in adults

Abstract: Introduction:Early diagnosis of acute kidney injury (AKI) remains a challenge. Recently, [TIMP-2]·[IGFBP7], which is a combination of urine tissue inhibitor of metalloproteinase 2 (TIMP-2) and insulin-like growth factor (IGF) binding protein 7 (IGFBP7), has been identified as a potential biomarker of AKI. We performed this meta-analysis to assess the diagnostic accuracy of urinary [TIMP-2]·[IGFBP7] for AKI in adult patients.Methods:We searched the PubMed, Embase, and Cochrane Library databases from database in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 38 publications
0
23
0
4
Order By: Relevance
“…Not unexpectedly, we identified a high percentage of patients (43 of 110, 39.1%) who exhibited TIMP-2 $ IGFBP7 greater than 0.3 (ng/mL) 2 /1,000 within 12 hours after cardiac operation but did not experience AKI. This biomarker cutoff is highly sensitive but not very specific for AKI, especially in low-risk patients [25]. In their aggregate, they imply that preoperative assessment of patients by the novel approach of RFR can identify patients at risk of AKI who are not currently identifiable by other means and who are likely to benefit from perioperative preventive measures or selection for biomarker monitoring to identify early AKI.…”
Section: Study Implicationsmentioning
confidence: 99%
“…Not unexpectedly, we identified a high percentage of patients (43 of 110, 39.1%) who exhibited TIMP-2 $ IGFBP7 greater than 0.3 (ng/mL) 2 /1,000 within 12 hours after cardiac operation but did not experience AKI. This biomarker cutoff is highly sensitive but not very specific for AKI, especially in low-risk patients [25]. In their aggregate, they imply that preoperative assessment of patients by the novel approach of RFR can identify patients at risk of AKI who are not currently identifiable by other means and who are likely to benefit from perioperative preventive measures or selection for biomarker monitoring to identify early AKI.…”
Section: Study Implicationsmentioning
confidence: 99%
“…Экспрессия TIMP-2 наблюдается и в нормальных, и в опухолевых тканях. Сывороточные уровни TIMP-2 повышены у пациентов с системным склерозом [5,6]. TIMP-4 экспрессируется на высоком уровне в сердце и на низком уровне -в почках, поджелудочной железе, толстой кишке и тестикулах.…”
Section: ингибиторы матриксных металлопротеиназunclassified
“…The diagnostic accuracy of the combination of the two proteins measured in urine has been shown to outperform numerous other potential biomarkers [68]. The expression of TIMP-2 and IGFBP-7 increases in the renal tubular cells (of distal and proximal tubule, respectively) in the early phase of cellular injury and their increase induces cell cycle arrest in G1 phase [69]. In the experimental study on rats, TIMP-2 and IGFBP7 in combination had better diagnostic accuracy for AKI that each marker alone [70].…”
Section: The Markers Of Tubular Dysfunctionmentioning
confidence: 99%
“…Similarly, in the American multi-centered study on 232 patients with sepsis, the area under ROC curve was 0.84 for the markers used in combination [71]. Metanalysis that was conducted by Liu et al [69] covering nine studies that were conducted throughout 2013–2016, encompassing 1886 adult patients from America and Europe, has proved the usefulness of combined TIMP-2 and IGFBP7 as reliable AKI markers, with the combined area under the ROC curve of 0.86. Another meta-analysis encompassing 10 prospective studies described by Su et al [72] has shown the diagnostic sensitivity of 0.84, specificity of 0.57, and area under ROC curve of 0.88.…”
Section: The Markers Of Tubular Dysfunctionmentioning
confidence: 99%